Designing Low Tortuosity Electrodes through Pattern Optimization for Fast‐Charging. Issue 4 (20th February 2023) - Wang, Ying; Zhang, Yuxuan; Cao, Daxian; Ji, Tongtai; Ren, Haoze; Wang, Guanyi; Wu, Qingliu; Zhu, Hongli
Abstract: The development of fast‐charging technologies is crucial for expediting the progress and promotion of electric vehicles. In addition to innovative material exploration, reduction in the tortuosity of electrodes is a favored strategy to enhance the fast‐charging capability of lithium‐ion batteries by optimizing the ion‐transfer kinetics. To realize the industrialization of low‐tortuosity electrodes, a facile, cost‐effective, highly controlled, and high‐output continuous additive manufacturing roll‐to‐roll screen printing technology is proposed to render customized vertical channels within electrodes. Extremely precise vertical channels are fabricated by applying the as‐developed inks, using LiNi0.6 Mn0.2 Co0.2 O2 as the cathode material. Additionally, the relationship between the electrochemical properties and architecture of the channels, including the pattern, channel diameter, and edge distance between channels, is revealed. The optimized screen‐printed electrode exhibited a seven‐fold higher charge capacity (72 mAh g −1 ) at a current rate of 6 C and superior stability compared with that of the conventional bar‐coated electrode (10 mAh g −1, 6 C) at a mass loading of 10 mg cm −2 . This roll‐to‐roll additive manufacturing can potentially be applied to various active materials printing to reduce electrode tortuosity and enable fast charging in battery manufacturing. Abstract : Low‐tortuosity electrodes with programmable patterns for fast‐charging Li‐ion batteries are achieved through screen printing. The well‐aligned channels promote ion transfer, increasing the reaction kinetic and guaranteeing high‐rate performance for fast charge. Screen printing is additive manufacturing with no waste generation and can be further scaled up to roll‐to‐roll manufacturing for the industrialization of low tortuosity electrodes.